METAPHOR AS A FACTOR OF DISCURSIVE CREATION (USING THE EXAMPLE OF THE LEXEME ВКУСНЫЙ – TASTY) - Olena V. Kardashova; Tetiana F. Filchuk (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2023)
This article attempts a comprehensive discourse analysis of the metaphor using the lexeme “вкусный” (tasty) as an example. Considering that metaphor can be viewed from the perspective of its ability to create social reality, and that reality images are discursively conditioned, the authors explore metaphor as a discursive agent that implies information about the basic parameters of discursive instances: metasubject, metaobject, and meta-addressee. The tasks of discourse analysis of metaphor in the article include: 1) consecutive explication of metaphorically conditioned components of meaning; 2) reconstruction of the constitutive parameters of discursive instances of subject, object, and addressee, based on these components; 3) reconstruction of the worldview and articulatory possibilities of the speaker who occupies the position of discursive subject. The study was conducted on the material of the National Corpus of the Russian Language using descriptive, contextual, interpretative methods, and the method of component analysis. Discourse analysis of linguistic material allows for the reconstruction of two possible types of discursive subject. The first one (nominally designated as DS1) represents the subject as a prepared listener, viewer, appreciator, or expert. Its discursive orientation realizes such intentions as: recognition of the complexity and intrinsic value of objects in the surrounding world; readiness to expend one`s own resources to interact with them; existential needs to act as a subject of love, care, and knowledge; and transfer of the value center from one`s own “self” to the surrounding world. With such a focus, the source of positive emotions (“satisfaction”) becomes the discursive subject itself, which is characterized by the ability to valorize objects and endow them with meaning. These constitutive parameters of discursive subject DS1 are implicated in such metaphorical constructions as “tasty music”, “tasty picture”, “tasty space”, “tasty design solution”, “tasty movie”, “tasty goal”, “tasty opponent”, and so on. The second type of discursive subject (DS2) can be reconstructed based on metaphors like “tasty assets”, “tasty prices”, “tasty discounts”, “tasty offer”, “tasty text”, “tasty position”, “tasty option”, “tasty life”. Unlike DS1, its attitude towards things, phenomena, and events in the surrounding world is determined by the ratio of “resources spent – satisfaction received”, which characterizes the subject of this type as a consumer. The main intentional characteristics of DS2 are: a primary desire for satisfaction of their own needs and desires (receiving positive emotions, material benefits, achieving an attractive social status); the devaluation of the sovereign value of objects and the unwillingness to make an effort to interact with them; the devaluation of all qualities and properties inherent in an object, except for the consumer ones (capable of bringing satisfaction to the speaker); a fundamental unwillingness to expend their own resources, avoidance of novelty, and a desire to maintain the stability of their own internal and external space. These two configurations of discursive subject allow the speaker to articulate almost diametrically opposed attitudes towards the surrounding world. In general terms, they correspond to two worldviews: modernist and postmodernist.